Mosquito control workers in Malaysia: is lifetime occupational pesticide exposure associated with poorer neurobehavioral performance? - Yusof, Muhammad Zubir; Cherrie, John W; Samsuddin, Niza; Semple, Sean (Oxford University Press, 2022)
Background Use of pesticides has been linked to neurobehavioral deficits among exposed workers. In Malaysia, organophosphate and pyrethroid pesticides are commonly used to control mosquito-borne diseases.